The Influence of Education Through The Landlord's Game on Level of Knowledge About Sexual Violence - Aulia Rizqi Nabella; Mariyati Mariyati (The International Science of Health Journal, 2024)
Cases of sexual violence in Indonesia continue to increase year by year, and the victims are not only adults but also involve children. This incident is the impact of the lack of educational game education from an early age. The purpose of this study is to determine the influence of education through The Landlord's game on the level of knowledge of sexual violence. This type of research uses quantitative research using a quasi-experimental design with a one-group pretest posttest approach. The researcher used a random sampling technique with 256 research subjects. The simple sample technique in the study used the purposive sampling method which was calculated with the slovin formula and produced as many as 38 samples. The test used is the Wilcoxon test. The results of the bivarat test showed that Z calculated -3.766 and the p-value was 0.000 < 0.05. So it can be concluded that if p-value = 0.000 < 0.05, it means that there is an influence of education through the landlord's game on the level of knowledge of sexual violence at SMA Negeri 6 Semarang City.